Administrative and legal principles of the ministry of digital transformation of Ukraine - Zakrynytska, Viktoriia; Plotnikova, Kateryna (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2023)
Introduction. Modern digitization is developing simultaneously along its three key vectors: information society; digital economic relations; e-government. Information processes in modern society encourage central bodies of executive power to update their own activities. The relevance is due to the fact that society’s demand for digitization, the opening of national electronic resources and the introduction of electronic services are the main challenges for reforming the state digital policy. One of the rather important steps in the digitalization of society and the state was the creation of the Ministry of Digital Transformation of Ukraine in 2019. The goal is to clarify the administrative and legal basis of the activity of the Ministry of Digital Transformation of Ukraine. Methods. Theoretical and general scientific (analysis, synthesis, systematization), empirical method. Main results of the research. The article is devoted to a theoretical study of the peculiarities of the administrative and legal foundations of the Ministry of Digital Transformation of Ukraine. It was determined that the Ministry of Digital Transformation of Ukraine has clearly defined goals, tasks and powers, and justified the implementation of public administration in the field of electronic governance. The tasks of the ministry are systematized according to key areas such as: tasks of state administration; public service tasks; task of stimulating entrepreneurship. The conclusions. The Ministry of Digital Transformation of Ukraine is the central certification body in the field of electronic trust services. The development of broadband access to the Internet, telecommunications networks and the IT industry is also within the competence of the Ministry. Having analyzed the tasks and powers of the Ministry of Digital, the main among them are administrative and national ones, which form the main layer of its activity and ensure its essence.